COMPREHTNSIVE APPROACH TO PILONIDAL SINUS TREATMENT - P. M. Lavreshin; V. K. Gobedzishvili; S. S. Korablina; V. V. Gobedzishvili; O. V. Vladimirova; H. M. Baichorov (Медицинский вестник Юга России, 2014)
Purpose: to improve results of treatment of patients with pilonidal sinus by developing and implementing of some modifications of operationsMatherials and methods: 267 patients with different clinical forms of pilonidal sinus were underwent surgical treatment. A new treatment strategy and some modification of operations are studied.Results and Summary: it’s necessary to identify risk groups of excessive (pathological) scarring and administer antiscarring treatment among the patients with pilonidal sinus. It is shown that such a treatment strategy has significantly improved the patients outcome with pilonidal sinus: the number of relapses reduced from 8,1% to 2,4%;discomfort phenomenon as a result of rough scar deformation in the sacrococcygeal region from 21,8% to 7,3%; number of patients with persistent recovery increased from 91,9% to 95,3%;time of hospital cure reduced in the main group in average:a stage without inflammation on 1,7 b/d(bad day), in remission stage – 2,1 b/d; in the stage of chronic inflammation – 2,6 b/d.